Determination of Montelukast Sodium by flow injection chemiluminescence - Omar Adnan Hashem; Semaa Hamed Ahmad; Sabreen Shakeir Mahmood (Tikrit Journal of Pure Science)
This study  includes determination Montelukast sodium by using flow injection chemiluminescence technique, the optimum concentrations were (150) ppm of magnesum ion, (5×10-4) M luminol, (0.001) M  hydrogen peroxide, linearity of concetraction (0.1-0.001) M  that give the highest luminescence intensity, and correlation cofficient was  (0.9054), The relative standard deviation  RSD% (2.3) and detection limit (0.0001) M and  relative error (0.018) ,the percent recovery (97%).